Phospho-Proteomic Discovery of Novel EPO Signal Transducers Including TXNIP as a Mediator of EPO- Dependent Human Erythropoiesis - Held, Matthew A. (Exp Hematol, 2020)
Erythroid cell formation critically depends upon signals transduced via EPO/EPOR/JAK2 complexes. This includes not only core response modules (e.g., JAK2/STAT5, RAS/MEK/ERK), but also specialized effectors (e.g., Erythroferrone, ASCT2 glutamine transport, Spi2A). By employing phospho-proteomics and a human erythroblastic cell model, we presently identify 121 new EPO target proteins, together with their EPO- modulated domains and phosphosites. Gene Ontology enrichment for ‘Molecular Function’ identified adaptor proteins as one top EPO target category. This includes a novel EPOR/JAK2-coupled network of actin assemblage modifiers, with adaptors DLG-1, DLG-3, WAS, WASL and CD2AP as prime components. ‘Cellular Component’ GO analysis further identified 19 new EPO- modulated cytoskeletal targets including the erythroid cytoskeletal targets SPECTRIN-A, SPECTRIN–B, ADDUCIN-2 and GLYCOPHORIN-C. In each, EPO-induced phosphorylation occurred at p-Y sites and subdomains that suggest coordinated regulation by EPO of the erythroid cytoskeleton. GO analysis of ‘Biological Processes’ further revealed metabolic regulators as a likewise unexpected EPO target set. Targets included ALDOLASE-A, PYRUVATE DEHYDROGENASE-A1 and THIOREDOXIN- INTERACTING PROTEIN (TXNIP), with EPO-modulated pY-sites in each occurring within functional subdomains. In TXNIP, EPO- induced phosphorylation occurred at novel p-T349 and p-S358 sites, and was paralleled by rapid increases in TXNIP levels. In UT7epo-E and primary human HSC-derived erythroid progenitor cells, lentivirus-mediated shRNA knockdown studies revealed novel pro-erythropoietic roles for TXNIP. Specifically, TXNIP’s knockdown sharply inhibited c-KIT expression; compromised EPO dose-dependent erythroblast proliferation and survival; and delayed late-stage erythroblast formation. Overall, new insight is provided into EPO’s diverse action mechanisms, and TXNIP’s contributions to EPO-dependent human erythropoiesis.